Escola do campo, currículo e práticas agroecológicas: um estudo sobre a escola família agrícola (EFA) Dom Fragoso - Lima, Maria Patrícia Moura de (2017)
The rural school has developed an emancipatory education that teaches the farmers’ children how to deal with the land and the environment creatively, innovatively and independently of factors external to their property and that provides them with the knowledge of ethical, moral and intellectual values and means of coexistence with the semi-arid region of Ceará, Brasil. This study aims to understand how the curriculum of the Agricultural Family School (EFA) Dom Fragoso, in Independência, Ceará, based on the Alternance Pedagogy, develops in the hinterland of Inhamuns agro-ecological techniques of living in the semi-arid. The research in question takes the qualitative approach from the dialectical perspective to understand how in basic education popular knowledge is related to the educational process in a productive way. In an attempt to better understand the universe of Alternance Pedagogy based on agroecology and the fundamentals that guide Field Education, we have as reference the studies of Arroyo (2009 - 1999); Caldart (2004); Mészáros (2008). Among the authors that work with curriculum we refer to Freire (2004); Apple (2006); Mclaren (1991); Freire (2005). Regarding Agroecology, the studies of Altieri (2004) and Gadotti (2009), among others, were used. Our intention is not only to investigate how or if the curriculum of the analyzed rural school contributes to the insertion of agroecological practices in the semi-arid region, but also seeks to understand how the EFA has been developing the agroecological practices proposed in the curriculum in the current dryseason. In the course of the research, it was verified that the EFA has sought alternatives for development to the semi-arid, linked to the foundations of agroecology directed to family agriculture and brings as one of its basic concepts, the liberating, inspired education of Paulo Freire. It is concluded, therefore, that in spite of the lack of assistance, the school has developed alternatives of living with the semi-arid region, working with its limitations, and with the desire to provide the sertanejos with a dignified and healthy life.